Acceleration of thrombolysis with ultrasound through the cranium in a flow model - Spengos, Konstantinos; Behrens, Stephan; Daffertshofer, Michael; Dempfle, Carl-Erik; Hennerici, Michael G. (Ultrasound in medicine & biology, 2000)
Thrombolysis is an efficient therapy for hyperacute stroke within a limited time window. Neurological outcome depends on the recanalization time of the occluded vessel. Nonthermal effects of low-frequency ultrasound (US) accelerate enzymatic fibrinolysis in vitro. We examined the effects of transcranially applied US on recombinant tissue plasminogen activator (rt-PA)-mediated thrombolysis in a flow model in vitro. Pure fibrin clots were placed in a continuous-pressure flow model and treated with rt-PA during 1-MHz US exposure (0.5 W/cm(2); spatial peak, temporal peak intensity). Transcranial and direct US application in combination with rt-PA significantly (p<0.001) shortened recanalization time, increased perfusion flow and reperfusion rate in comparison with rt-PA-mediated thrombolysis alone. Recanalization rate within 30 min was 90-100% in the US-exposed clots vs. 30% in the clots treated only with rt-PA. Our results suggest that transcranial application of 1-MHz US may accelerate reperfusion and recanalization rate of occluded intracerebral vessels by enhancing rt-PA-mediated thrombolysis. Shortening of recanalization time could contribute to optimizing effects of acute thrombolytic stroke therapy.